DAMPAK PENGGUNAAN CODE SWITCHING (CS) DAN CODEMIXING (CM) PADA SISWA SMP MELALUI PENDEKATAN BILINGUAL TEACHING CLASSROOM - Nofiana S; Nurjannah; Riska (Jurnal Semantik, 2023)
The purpose of the research is to find out the form and impact of using code switching and code mixing on SMPN 1 Peukan Pidie students through the bilingual teaching classroom approach. The method used is qualitative method. The data source is the teacher at SMPN 1 Peukan Pidie. The data in this study are code switching and code mixing. Data collection techniques using observation, interview and recording techniques. Data analysis techniques in this study are, (1) looking back at the results of observations and looking back at the results of interviews that have been conducted, (2) playing back the recording results, (3) identifying formulating, classifying, and describing usage data. The results of this study can be concluded that SMPN 1 Peukan Pidie school applies a bilingual teaching classroom approach. Here the teacher uses local language as the bilingual foundation. The impact of using code switching and code mixing on students of SMPN 1 Peukan Pidie through the bilingual teaching classroom approach is that it makes it easier for students to understand the material, shows self-identity, can change the atmosphere to be relaxed and become closer to students both in class and outside the classroom.